Clinical evaluation of time‐of‐flight MR angiography with sparse undersampling and iterative reconstruction for cerebral aneurysms. (10th August 2017) - Fushimi, Yasutaka; Okada, Tomohisa; Kikuchi, Takayuki; Yamamoto, Akira; Okada, Tsutomu; Yamamoto, Takayuki; Schmidt, Michaela; Yoshida, Kazumichi; Miyamoto, Susumu; Togashi, Kaori
Abstract : Compressed sensing (CS) MRI has just been introduced to research areas as an innovative approach to accelerate MRI. CS is expected to achieve higher k ‐space undersampling by exploiting the underlying sparsity in an appropriate transform domain. MR angiography (MRA) provides high spatial resolution information on arteries; however, a relatively long acquisition time is necessary to cover a wide volume. Reduction of acquisition time by CS for time‐of‐flight (TOF) MR angiography (Sparse‐TOF) is beneficial in clinical examinations; therefore, the clinical validity of Sparse‐TOF needs to be investigated. The aim of this study was to compare the diagnostic capability of TOF MRA between parallel imaging (PI)‐TOF with an acceleration factor of 3 (annotated as 3×) and Sparse‐TOF (3× and 5×) in patients with cerebral aneurysms. PI‐TOF (3×) and Sparse‐TOF (3× and 5×) imaging were performed in 20 patients using a 3 T MRI system. Aneurysms in PI‐TOF (3×) and Sparse‐TOF (3× and 5×) were blindly rated as visible or scarcely visible by neuroradiologists. The neck, height and width of aneurysms were also measured. Twenty‐six aneurysms were visualized and rated as visible in PI‐TOF (3×) and Sparse‐TOF (3× and 5×), with excellent agreement between two raters. No significant differences were found in measured neck, height or width of aneurysms among them. Sparse‐TOF (3× and 5×) were acquired and reconstructed within 6 min, and cerebral aneurysms were visible in both of them with equivalent quality to PI‐TOF (3×). Sparse‐TOF (5×) is a good alternative to PI‐TOF (3×) to visualize cerebral aneurysms. Abstract : This study is the first study of clinical validation for cerebral aneurysm detection on prospectively acquired compressed sensing MRA sequences (Sparse‐TOF). Sparse‐TOF 3× and 5× were acquired and reconstructed with clinically acceptable time, and cerebral aneurysms were visible in both Sparse‐TOF 3× and 5× with equivalent quality to parallel imaging (PI)‐TOF, with excellent agreement between two neuroradiologists.